CHICKEN ON A RESERVATION SYSTEM MULTAJAM BROKER APPLICATION USING MS ACCESS 2000 - Zulkarnain Zulkarnain; Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Information technology in the world is growing rapidly, and therefore every humanbeing must follow the information technology development in order not left behindbyothers.Current computer is a primary need for someone who does not want to catch theprogress of information technology, inside covers will need to process all forms ofhuman form job that takes time and results accurately and quickly.Applications reservation on the broker Multazam chicken is one application that canfacilitate and be able to make easy chicken problem for entrepreneurs in order torecord, procesed and print all forms of transactions done every day quickly andprecisely for entrepreneurs can make decisions and subsequent policy will be taken.